Handbook of protocols for standardized measurements of floral traits for pollinators in temperate communities - Alice Michelot‐Antalik; Alban Langlois; Francesco deBello; James Desaegher; Léa Genty; Jérémie Goulnik; Jérémy Grosjean; Anne‐Laure Jacquemart; Alan Kergunteuil; Robert R. Junker; Léna Jeannerod; Jean‐François Odoux; et al. (Methods in Ecology and Evolution)
Abstract Floral traits describe organs or structures directly related to plant reproduction, and they are essential to understanding plant–pollinator interactions, notably for conservation purposes. The growth of plant trait‐based approaches lies in the availability of data shared by the international research community on dedicated platforms, as well as in protocols compiled in handbooks on how to measure these traits in a standardized way. Floral traits are important pieces that are missing from these handbooks, likely due to the complexity of flower morphology. Here, we present a handbook of standardized protocols dedicated to floral traits that can be applied to a wide set of temperate plant species to quantify these traits at the scale of plant communities. The 24 floral traits are grouped into three categories: visual and olfactory cues, accessibility and resources. We also provide four additional features related to flower abundance and phenology that we recommend measuring to scale up individual species' trait values to overall plant communities. By collecting these floral traits in a standardized way, we promote applications in the context of community ecology to predict the diversity of pollinator communities, identify the effects of environmental changes and study plant–pollinator networks.